2007
DOI: 10.1111/j.1600-0447.2007.01032.x
|View full text |Cite
|
Sign up to set email alerts
|

Yoga therapy as an add‐on treatment in the management of patients with schizophrenia – a randomized controlled trial

Abstract: Both non-pharmacological interventions contribute to reduction in symptoms, with YT having better efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
267
4
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(285 citation statements)
references
References 24 publications
8
267
4
5
Order By: Relevance
“…Duraiswamy et al assigned schizophrenic men to 20 weeks of yoga or walking intervention. 34 At the end of the study, the authors observed improved quality of life outcomes for both groups. In other populations, improvement of quality of life outcomes have been observed in non-schizophrenic subjects who performed 6 months of resistance exercise.…”
Section: Discussionmentioning
confidence: 87%
“…Duraiswamy et al assigned schizophrenic men to 20 weeks of yoga or walking intervention. 34 At the end of the study, the authors observed improved quality of life outcomes for both groups. In other populations, improvement of quality of life outcomes have been observed in non-schizophrenic subjects who performed 6 months of resistance exercise.…”
Section: Discussionmentioning
confidence: 87%
“…aerobic exercise) [45][46][47]. However, in all these yogastudies a brief supervised period was followed by a longer unsupervised study period (with lack of adherence data) making it difficult to compare similar physical activity volumes.…”
Section: What Is the Optimal Physical Activity Prescription For Peoplmentioning
confidence: 99%
“…Several studies from India over the past decade 3 have reported that yoga has beneficial effects on schizophrenia, both with regard to 'positive' (psychotic) symptoms and 'negative' symptoms (such as lack of motivation or enjoyment), for which there are few effective treatments (see 'Negative feedback' , page S10). Researchers have previously reported that both physical exercise and psychotherapy (including 'mindfulness' techniques such as meditation) can ease the symptoms of schizophrenia.…”
Section: Cultural Contextmentioning
confidence: 99%